Empowering education among asnaf through distribution of zakat from the perspective of maqasid syariah - Ismail, Halim; Ismail, Noor Azizi (Akademi Zakat (AZKA), 2022)
This study examines the empowerment of education among the asnaf through the distribution of zakat according to the perspective of maqasid syariah. This study presents the debate of scholars regarding the distribution of zakat to strengthen the education of asnaf and its implementation in Malaysia. This study was conducted using content analysis methods through deductive, inductive, and comparative methods. Studies show that, through the perspective of maqasid syariah, the distribution of zakat to asnaf can increase the level of education of this group.